Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Sure, let's solve the equation step by step.
We start with the given equation:
[tex]\[ x - 2x - \left(\frac{3x - 4}{7}\right) = \left(\frac{4x - 27}{3}\right) - 3 \][/tex]
1. Combine like terms on the left-hand side:
[tex]\[ x - 2x = -x \][/tex]
So the equation becomes:
[tex]\[ -x - \left(\frac{3x - 4}{7}\right) = \left(\frac{4x - 27}{3}\right) - 3 \][/tex]
2. Clear the fractions by finding a common denominator for the entire equation.
- The common denominator for the terms involving fractions can be found from 7 and 3, which is 21.
3. Rewrite the equation by multiplying all terms by 21 to eliminate the fractions:
[tex]\[ 21 \left(-x - \frac{3x - 4}{7}\right) = 21 \left(\frac{4x - 27}{3} - 3\right) \][/tex]
4. Distribute 21 inside the parentheses:
[tex]\[ 21(-x) - 21 \left(\frac{3x - 4}{7}\right) = 21 \left(\frac{4x - 27}{3}\right) - 21 \cdot 3 \][/tex]
5. Simplify each term:
[tex]\[ 21(-x) - 3(3x - 4) = 7(4x - 27) - 63 \][/tex]
6. Distribute inside the parentheses:
[tex]\[ -21x - (9x - 12) = 28x - 189 - 63 \][/tex]
7. Simplify both sides of the equation:
[tex]\[ -21x - 9x + 12 = 28x - 252 \][/tex]
8. Combine like terms:
[tex]\[ -30x + 12 = 28x - 252 \][/tex]
9. Move all terms involving [tex]\( x \)[/tex] to one side and constant terms to the other side:
[tex]\[ -30x - 28x = -252 - 12 \][/tex]
[tex]\[ -58x = -264 \][/tex]
10. Solve for [tex]\( x \)[/tex] by dividing both sides by -58:
[tex]\[ x = \frac{-264}{-58} \][/tex]
[tex]\[ x = \frac{264}{58} \][/tex]
[tex]\[ x = \frac{132}{29} \][/tex]
So the solution to the given equation is:
[tex]\[ x = \frac{132}{29} \][/tex]
We start with the given equation:
[tex]\[ x - 2x - \left(\frac{3x - 4}{7}\right) = \left(\frac{4x - 27}{3}\right) - 3 \][/tex]
1. Combine like terms on the left-hand side:
[tex]\[ x - 2x = -x \][/tex]
So the equation becomes:
[tex]\[ -x - \left(\frac{3x - 4}{7}\right) = \left(\frac{4x - 27}{3}\right) - 3 \][/tex]
2. Clear the fractions by finding a common denominator for the entire equation.
- The common denominator for the terms involving fractions can be found from 7 and 3, which is 21.
3. Rewrite the equation by multiplying all terms by 21 to eliminate the fractions:
[tex]\[ 21 \left(-x - \frac{3x - 4}{7}\right) = 21 \left(\frac{4x - 27}{3} - 3\right) \][/tex]
4. Distribute 21 inside the parentheses:
[tex]\[ 21(-x) - 21 \left(\frac{3x - 4}{7}\right) = 21 \left(\frac{4x - 27}{3}\right) - 21 \cdot 3 \][/tex]
5. Simplify each term:
[tex]\[ 21(-x) - 3(3x - 4) = 7(4x - 27) - 63 \][/tex]
6. Distribute inside the parentheses:
[tex]\[ -21x - (9x - 12) = 28x - 189 - 63 \][/tex]
7. Simplify both sides of the equation:
[tex]\[ -21x - 9x + 12 = 28x - 252 \][/tex]
8. Combine like terms:
[tex]\[ -30x + 12 = 28x - 252 \][/tex]
9. Move all terms involving [tex]\( x \)[/tex] to one side and constant terms to the other side:
[tex]\[ -30x - 28x = -252 - 12 \][/tex]
[tex]\[ -58x = -264 \][/tex]
10. Solve for [tex]\( x \)[/tex] by dividing both sides by -58:
[tex]\[ x = \frac{-264}{-58} \][/tex]
[tex]\[ x = \frac{264}{58} \][/tex]
[tex]\[ x = \frac{132}{29} \][/tex]
So the solution to the given equation is:
[tex]\[ x = \frac{132}{29} \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.